Students’ Attitude Towards Distance Learning - Puspitasari, Armyta; Ramadhan, Rizky (Universitas Pahlawan Tuanku Tambusai, 2023)
This article aimed at knowing the attitude of distance learning to the Diploma students of Indonesian Railway Polytechnic. The objective of the study was to explore the students’ attitude towards distance learning, the advantages and disadvantages of distance learning. The method used in this study were both qualitative and quantitative method to reveal students’ attitude towards distance learning. The research participants of this study were the fifth semester students. After analyzing the data, it can be concluded that based on the result of the study that has been analyzed, it was seen that the students’ attitude towards distance learning was overall positive. And the advantages of distance learning are 1) More effective to learn independently, 2) Easier to manage the time 3) More familiar with the technology, and 4) Flexibility. While the disadvantages of distance learning are; 1) Harder to feel motivated and students’ boredom, 2) Difficult to get socialized with friends and to get feedback from the lecturer directly, 3) More theoretical then practical, 4) Hard to focus and many distractors such as internet connection or black out, and 5) More tasks and assignments.